2015
DOI: 10.1002/ep.12170
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and effects of two algicidal isolates on antioxidase activities of Chlorella pyrenoidosa

Abstract: With increasing water pollution, algal bloom becomes more and more frequent. To manage algal blooms, the exploitation and study of novel algae-lysing strains are extremely urgent. In this study, two algicidal isolates (NP23 and AM11) against Chlorella pyrenoidosa were obtained from the Baiguishan reservoir in China. Phylogenetic analysis of the 16S rDNA sequences revealed that isolates NP23 and AM11 were closely related to Enterobacter cloacae and Gibberella moniliformis, respectively. Moreover, to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…CAT is one of the most important enzymes in the antioxidant system. It could promote decomposition and prevent the accumulation of harmful H 2 O 2 in cells [54]. In our study, the supernatant of Sp34 significantly increased the CAT activity, thus decomposing H 2 O 2 and mitigating the oxidative damage to algal cells [55].…”
Section: Discussionsupporting
confidence: 51%
“…CAT is one of the most important enzymes in the antioxidant system. It could promote decomposition and prevent the accumulation of harmful H 2 O 2 in cells [54]. In our study, the supernatant of Sp34 significantly increased the CAT activity, thus decomposing H 2 O 2 and mitigating the oxidative damage to algal cells [55].…”
Section: Discussionsupporting
confidence: 51%
“…predominantly aimed at cyanobacteria, alga-lytic activity of Enterobacter spp. expands also to green algae [ 58 60 ]. Since both cyanobacteria and green algae were present in the feedstock for the described here AD in a UASB reactor (see Materials and Methods), we can suggest that members of Pseudomonadales and Enterobacteriales orders have an alga-lytic activity towards microalgal biomass from Logan Wastewater Lagoons.…”
Section: Discussionmentioning
confidence: 99%
“…At light intensities of 2500 lx and 4500 lx, CAT activity was lowest at 0 rpm water disturbance (Figure 1c), algal cell density was also lowest, which indicated that increasing appropriate water disturbance is beneficial for enhancing enzyme activity in algal cells to promote algal growth. Liao et al observed that the trend in CAT was the same as the density of algal cells during cultivation (Liao et al, 2015). Thus, algal cells may not grow and reproduce normally when cells contain less CAT.…”
Section: Resultsmentioning
confidence: 99%